Procrastinación laboral y rasgos de personalidad en trabajadores de una entidad financiera - Valdivia Vásquez, Juan Gabriel (2024)
This research aimed to determine whether there is a relationship between procrastination at work and one of the Big Five personality traits in employees of a financial institution in the Arequipa region. 414 workers were evaluated, 274 women and 140 men, between 20 and 55 years old, 187 married or living together, 219 single, 7 divorced and one widowed, all of them working in the administrative, credit and operation areas. The research design was correlational. The “Procrastination at Work Scale” (PAWS) from Metin et al. (2016), adapted by Guzmán and Rosales (2017), and the NEO Personality Inventory from Costa and McCrae, in its short version (NEO-FFI), adapted by Martínez and Cassaretto (2011) were employed. It was found that procrastination at work is low, which does not represent a problematic situation for the company. However, it was shown that there is a statistically significant positive correlation between neuroticism and procrastination at work and a significant negative correlation between conscientiousness and procrastination. It was also found that women demonstrated less procrastination than men, that procrastination decreased as age increased, that around loans there was more neuroticism and, in the administrative area, more conscientiousness.